Sweet escape: The role of empathy in social media engagement with human versus virtual influencers - Mirowska, Agata; Arsenyan, Jbid (International journal of human-computer studies, 2023)
•People use social media for various purposes, including emotional diversion.•Influencers on social media share emotions to build connections with users.•Virtual influencers emulate similar emotions to human influencers.•Virtual influencers may provide escape from emotional experience.•“Escapism effect” where high empathy users prefer virtual influencers. Virtual influencers engage in emotional sharing to gain and keep followers. However, given that many people use social media for diversion purposes, this emotional sharing may hinder users’ ability to escape from everyday emotional experiences, particularly for highly empathetic individuals. Using a between subjects, randomised experimental design, we explore how empathy affects reactions to virtual vs. human influencers, showing that those highest on empathy are more likely to follow a virtual influencer, and rate her as more socially attractive, than a comparable human influencer; these results disappear when the influencers’ true nature is unknown to participants. We postulate that these results represent an “escapism effect”, where the virtual influencer is expected to provide greater diversionary benefits from everyday human emotional experiences and require fewer cognitive resources in the form of emotional sense making. We present practical implications and future research opportunities arising from this effect.